ISOTOPIC AGES OF THE I TYPE GRANITESIN WEST JUNGGAR SAWUER REGION - Yuan F.; Zhou T.F.; Tan L.G.; Fan Y.; Yue S.C.; Yang W.P.; He L.X. (My University, 2006)
Sawuer region is located in west Junggar, Jimunai County of Altay district and Hefeng county of Tacheng district, Xinjiang. The region is along the north margin of Kazakstan-Junggar plate. The intrusions (mainly acid) are widespread. The Sentasi intrusion, the Wokensala intrusion and the Tasite intrusion are mainly adamellite. According to SHRIMP U-Pb age analysis results, the crystallization age of Sentasi intrusion is 328.2±5.7Ma(1σ) and that of Wokensala intrusion is 323.8±6.2Ma(1σ), and the age of Tasite intrusion is 313.6±3.2Ma(1σ) with 40Ar/39Ar age analysis results, corresponding to the afternoon of early Carboniferous. The intrusions belong to I type granite and are the partial alkali rock. The Nd, Sr, Pb isotope compositions of the intrusions indicate a mantle source, while the δ18O values are normal. The intrusions belong to post-collisional granite, indicating that the Sawuer region indeed west Junggar was in the post-collisional setting in the afternoon of early Carboniferous. They might form in the extrusion to extension period of the post-collisional stage. The geochemistry characteristics of the Sentasi, Wokensala and Tasite intrusions are similar to those of known I type granites formed at about 300Ma in Junggar. The post-collisional I type granites must begin to form in the afternoon of early Carboniferous in Junggar. The confirmation of post-collisional I type granites of afternoon of early Carboniferous in the Sawuer region provides new evidence for the regional vertical continental growth in late Paleozoic.
Keywords: 40AR/39AR DATING; GRANITE; POST-COLLISIONAL; SAWUER REGION; SHRIMP; XINJIANG; ZIRCON; Палеозой::Каменноугольная; Paleozoic::Carboniferous